Information, Meaning and the role of Semiosis in the Development of Living Systems - Liszka, James Jakób (Signs - International Journal of Semiotics, 2008)
The claim here is that semiosis is concomitant with life and not simply one of several possible adaptive mechanisms. Signs, particularly indices, serve as steering mechanisms for even the most primitive organisms, completing a circuit between the detection of energy sources and behavior that is conducive to acquiring those sources. Without that kind of agency, no form of life is possible. To show this, an understanding of the interrelation among energy, matter, information, and meaning is required, and how they are interlaced in the notion of work. One specific thesis of the paper in this respect is that meaning is the propagating work of information. Peirce’s theory, with some modifications, can be used to articulate this account of things, and brings a powerful analytical tool to the problem.